Informazione e massificazione: il deficit educativo. Eravamo davvero pronti? - Zaffino, Elisabetta Bruna (Derecom. Revista Internacional de Derecho de la Comunicación y de las Nuevas Tecnologías, 2024)
In this paper, we seek to focus on a phenomenon of unstoppable expansion such as the use of the Internet networks in the information and communications system. What we propose to highlight here is the consequences that may derive from an unsustainable use of this tool. The Internet, as a vehicle of obvious importance in many realities, has contributed to improving the social conditions of men. Just think of the simplified access to information or of the recognition of personal moments of expression that have led many socio-political debates horizontally up to the creation of platforms that allow expressing opinions on the work of certain ruling classes. The global dimension of the phenomenon and its ability to penetrate the social fabric has encouraged the masses to enter the circle of opinion leaders, generating an inversion of the tendency of information itself, so that by means of the asseveration of freedom and symbol of collapse of the barriers its use has denied the original libertarian design facilitating disinformation, propaganda and populism, in a vicious circle of visibility at any cost that involves mass media, governments, organizations and users themselves. The mobilization towards this type of information has also shifted propaganda to a terrorist and criminal background, facilitating the transmission of messages and recruitment activities and benefiting from the greatest difficulties of the investigative departments. The theory we are trying to report is based on a setback that leads to the search for a center of gravity of social and cultural balance that moves from personal awareness and requires a management system that knows how to ring a new concept of education and training towards individuals, able to relate and face the challenges that cyber-space poses. La teoria che si cerca di riportare è basata su una battuta di arresto che conduca alla ricerca del proprio baricentro di equilibrio sociale e culturale che passi dalla consapevolezza personale e che pretenda un sistema di gestione che sappia inanellare un nuovo concetto di educazione e formazione verso individui in grado di relazionarsi ed affrontare le sfide che il cyber- spazio sottopone.